Theatricality of Andean baroque art - Grupp Catello, Franz (2007)
The Spanish poet Calderón de la Barca is one of the authors who has best represented the feeling of human life during the Baroque period. In his work The Great Theater of the World, premiered in 1645, Calderón placed man acting on a great stage before God the Father and his entire heavenly court; the play that the man performed was his own life, and the stage for this performance was the world. This metaphor of the theater of the world will transcend the entire era.